Strategies for Integrated Audits to Ensure Control, Risk Management, and Ethical Practices - Wahyuni, Wahyuni; Astuti, Widia; Fitriyani, Fitriyani; Christianty, Maylani; Septanti, Rizky Wahyu (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
The purpose of this study is to examine the role of integrated audits in organizational governance and ethical practices. Through a systematic literature review, the research design entails identifying relevant academic journals, industry reports, and scholarly publications related to integrated audits, organizational governance, and audit effectiveness. The selected literature will be critically evaluated to identify key themes, trends, and theoretical frameworks, with thematic analysis used to uncover recurring patterns. The findings reveal that integrated audits play a pivotal role in fortifying organizational resilience, promoting sustainable business practices, and enhancing stakeholder trust. From a strategic management perspective, integrated audits provide valuable insights for decision-making and resource allocation, while ethically, they foster a culture of accountability and transparency. The integration of emerging technologies such as artificial intelligence and blockchain further enhances audit effectiveness. The implications of this research underscore the need for organizations to embrace integrated audits as a strategic imperative for enhancing governance, risk management, and ethical practices. This study contributes to the advancement of knowledge in the field of integrated audits and informs organizational practices in navigating the complexities of the modern business landscape.